Effect of Health Education Using WhatsApp Group on Knowledge About Visual Inspection Acetate Test - Rambe, Rizka Sititah; Amra, Ricca Nophia; Bancin, Fitriani (Journal of Maternal and Child Health, 2023)
Background:  According to the World Health Organization (WHO) in 2016 nearly 9 million women died from cervical cancer. Public awareness to detect early the disease is low. Visual Inspection Acetate (VIA) test for cervical cancer is considered a taboo solution. Women feel embarrassed to carry out VIA examination. Research is lacking whether health education through communication media using WhatsApp groups is effective. This study aimed to determine the effect of health education using WhatsApp group on knowledge about cervical cancer and VIA. Subjects and Method: This was a quasi-experiment with one group pre-test and post-test design, conducted at the Simpang Kiri Health Center in February 2023. A total of 98 women of reproductive age were selected for this study. The dependent variable was knowledge about cervical cancer and VIA. The independent variable was health education using WhatsApp group. The data were collected by questionnaire. The mean difference of knowledge before and after WhatsApp group education was tested by paired t-test. Results: The mean score of knowledge about VIA after WhatsApp group education was higher (Mean= 16.61; SD= 3.24) than before (Mean= 11.35; SD= 1.69), and this was statistically significant (p = 0.011). Conclusion: WhatsApp group education is effective to improve knowledge about cervical cancer and VIA among women of reproductive age. Keywords: WhatsApp, education, knowledge, visual acetate inspection. Correspondence: Rizka Sititah Rambe. Midwifery Academy of Medica Bakti Persada. Jl. Pinang Baris Desa Lae Oram Dusun Indah No. 193, Simpang Kiri, Subulussalam, 24781, Aceh, Indonesia. Email: ramberizka76@gmail.com. Mobile: 082363695492.